Beyond the individual-systemic binary: organizing belief in the rhetoric of anti-sexual violence activism - Buisker, Lauren L., author; Gibson, Katie L., advisor; Long, Ziyu, committee member; Vasby Anderson, Karrin, committee member; Bubar, Roe, committee member (Colorado State University. Libraries, 2025)
This dissertation is a rhetorical history of anti-sexual violence activism that challenges what I refer to throughout the project as an "individual-systemic binary," a rhetorical tool of containment in sexual violence discourses that promotes cultural disbelief of survivors. The individual-systemic binary either isolates victims as individual anomalies or subsumes their stories into broad systemic critiques that flatten intersectional differences among victims and promote oppressive, carceral logics. In the aftermath of the Me Too movement, which I argue highlights the shortcomings of individual and systemic narratives surrounding sexual violence, this dissertation turns to intersectionally-informed, historical and contemporary anti-sexual violence organizing that offers insight about activist rhetorical strategies beyond the individual-systemic binary. To do so, I examine three case studies of U.S.-based anti-sexual violence advocacy, whose discourses offer prescriptive insight surrounding rhetorical resources for challenging rape culture. The first case study analyzes the 1944 movement on behalf of Recy Taylor, a Black survivor who multiple white perpetrators assaulted in Alabama. This campaign, called the Committee for Equal Justice for Mrs. Recy Taylor (CEJ), participated in what I term a "rhetoric of radical belief," which framed belief as an act of care, rather than an evaluation of a victim's credibility. Such rhetoric merged the individual-systemic binary by framing Taylor as an individual symbol of systemic democratic failure. The CEJ also inverted the binary by both individualizing the state responsible for ignoring Taylor and bestowing activists with systemic power. The second case study in this dissertation investigates the rhetoric of the 1970s movement against sexual harassment, which was comprised of working-class women, women of color, and university feminists who framed sexual harassment as a matter of economic exploitation. Through what I identify as a discourse that "(dis)organizes disbelief," the movement challenged rape culture scripts and shattered the individual-systemic binary by posing the organizational context as a third scale on which violence flourishes. Finally, the third case study of this dissertation centers around a contemporary nonprofit organization, anonymized as the Peer-Led Violence Prevention (PLVP) Program. Drawing upon the data from focus group interviews I conducted with workers in the PLVP, I argue that the PLVP constructs what I call a "belief biography," or a rhetoric that tracks how cultural belief in survivors is cultivated across time. This model of activism absorbs the strengths of both individual and systemic sides of the binary while avoiding their pitfalls, fostering change through localized, relational practice rather than top-down reform or punitive pressure. Ultimately, this dissertation situates belief in survivors not merely as a moral stance but as a cultural infrastructure requiring sustained rhetorical labor. This project contributes to rhetorical and organizational communication studies by mapping how advocacy efforts can cultivate cultural belief in survivors without reinscribing the hierarchies and exclusions that sustain sexual violence in the first place.